Simple singularities of multigerms of curves - Kolgushkin, P. A.; Sadykov, R. R. (Revista Matemática Complutense, 2001)
We classify stably simple reducible curve singularities in complex spaces of any dimension. This extends the same classification of irreducible curve singularities obtained by V. I. Arnold. The proof is essentially based on the method of complete transversals by J. Bruce et al.